Unlocking Young Minds : The Impact of Unplugged Coding on Elementary Students' Computational Thinking - Kasiono, Bagus; Pradhana, Galih; Huda, Nuril; Utami, Sri; Haerussaleh, Haerussaleh (Jurnal Paedagogy, 2025)
This study aims to analyze the effectiveness of the unplugged coding method in improving elementary students’ computational thinking skills, identify the CT components that develop, and evaluate its potential as a contextual, inclusive, and sustainable learning solution. This study employs a systematic literature review using the PRISMA technique, selecting 31 journal articles were indexed in reputable databases such as Scopus and SINTA published between 2021 and 2025. The articles were analyzed thematically based on relevance to CT and unplugged methods in elementary education. Results show that the unplugged coding method is an effective and contextually relevant approach to enhancing computational thinking (CT) skills in elementary school students. The effectiveness of this method is reflected in the development of key CT components and its positive contribution to student motivation and engagement in learning. Scientifically, these findings support the argument that strengthening CT does not necessarily rely on digital technology, but can be achieved through contextual and hands-on learning strategies. Therefore, unplugged coding has the potential to serve as a strategic alternative in primary informatics education, particularly in resource-constrained settings. As an implication, this study recommends the development of national teaching guidelines and policies to systematically support the integration of the unplugged approach into the curriculum. Further experimental research across diverse school contexts is needed to assess its long-term impact and to enrich best practices in implementation.